Covid-19 Lockdown and Fate of Migrant Labours in Delhi - Shahare, Virendra Balaji (Journal of Advanced Research in Humanities and Social Sciences, 2020)
Fifty Eight percent (approximately 63 lakh) migrant population in Delhi and NCR is currently employed in the unorganised sector. Nationwide lockdown due to COVID-19 pandemic across Delhi and NCR has created huge challenges, fear, insecurity and uncertainty among the people. Migrant workers are the worst affected and face huge challenges for their survival during lockdown. In this context the present paper discusses the socio-economic, psychological challenges faced by migrant workers such as accessing food, water, shelter and other necessary requirements. The paper examines the role and responsibilities of the government to protect the rights of migrant workers. It highlights the narratives of the migrant workers during lockdown. Some key questions have been raised to the governments with regards to protection of migrant workers. The research paper reviews the secondary data published in leading news papers, magazines and personal field observation made to understand the ground realities. The paper concludes that there is no simple answer to this tragic dilemma between two humanitarian crises, the spread of the virus and the devastation caused by the lockdown. How to cite this article: Shahare VB. Covid-19 Lockdown and Fate of Migrant Labours in Delhi. J Adv Res Humani Social Sci 2020; 7(1): 9-13. Orcid Id: https://orcid.org/0000-0002-3647-7674